RECONFIGURING INNOVATION PATHWAYS IN THE PUBLIC SECTOR: A DYNAMIC CAPABILITIES ANALYSIS OF LPDP AND PT KAI IN INDONESIA - Sugeng Bahagijo; Amirul Mustofa; Priyanto Priyanto (Journal Publicuho, 2025)
This study investigates how dynamic capabilities are developed and operationalised within two Indonesian public sector institutions: the Indonesia Endowment Fund for Education (LPDP) and the state-owned railway company, PT Kereta Api Indonesia (PT KAI). Using a qualitative comparative case study approach and drawing on Kattel’s (2022) public sector dynamic capabilities framework, sense-making, connecting, and shaping the research analyses institutional reports and documents from 2016 to 2023. LPDP exemplifies a design-led innovation model, characterised by long-term policy alignment, digital transformation, and inclusive scholarship and research funding mechanisms. In contrast, PT KAI demonstrates a crisis-driven transformation pathway involving operational restructuring, digital service reinvention, and physical infrastructure modernisation. The findings reveal that dynamic capabilities are highly context-sensitive and shaped by institutional form, leadership agency, and sectoral demands. This article contributes to the emerging literature on public sector innovation in developing countries by showing how different pathways of reform can produce adaptive, learning-oriented, and value-generating public institutions.